Behavioral Characterization of Individual Olfactory Memory Retrieval in Drosophila Melanogaster - CHABAUD, Marie-Ange; PREAT, Thomas; KAISER, Laure (Frontiers in Behavioral Neuroscience, 2010)
Memory performance depends not only on effective learning and storage of information, but also on its efficient retrieval. In Drosophila, aversive olfactory conditioning generates qualitatively different forms of memory depending on the number and spacing of conditioning trials. However, it is not known how these differences are reflected at the retrieval level, in the behavior of individual flies during testing. We analyzed conditioned behaviors after one conditioning trial and after massed and spaced repeated trials. The single conditioning produces an early memory that was tested at 1.5 h. Tested at 24h after training, the spaced and the massed protocols generate two different forms of consolidated memory, dependent or independent of de novo protein-synthesis. We found clearly distinct patterns of locomotor activity in flies trained with either spaced or massed conditioning protocols. Spaced-trained flies exhibited immediate and dynamic choices between punished and unpunished odors during the test, whereas massed-trained flies made a delayed choice and showed earlier disappearance of the conditioned response. Flies trained with single and spaced trials responded to the punished odor by decreasing their resting time, but not massed-trained flies. These findings demonstrate that genetically and pharmacologically distinct forms of memory drive characteristically different forms of locomotor behavior during retrieval, and they may shed light on our previous observation that memory retrieval in massed-trained flies is socially facilitated. Social interactions would enhance exploratory activity, and then reduce the latency of their conditioned choice and delay its extinction.